Nowe typy przestępstw lichwiarskich (art. 304 § 2 i 3 k.k.) a zasada subsydiarności prawa karnego - Giezek, Jacek; Lipiński, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The authors analyze new types of oﬀenses of Art. 304 § 2 and 3 CC, focusing on the issue of normative structures derived from criminal law (and other branches of law) and their mutual relations. Assuming that due to the principle of subsidiarity (ultima ratio) of criminal law, it is not possible to prohibit conduct previously not deemed unlawful by provisions of civil law, the authors conclude that the condition of liability for new “usury crimes” is determination of unlawfulness of the demanded interest or other costs of the loan, assessed from the perspective of civil law.
Keywords: pomocniczość prawa karnego; lichwa; ultima ratio; odsetki; retroaktywność prawa karnego